Study on Multi-Dimensional Paths of Green Manufacturing and Sustainable Development in Indonesia's Automotive Industry - Chengkang, Peng (Indonesian Journal Publisher, 2025)
With its long industrial chain and high correlation, the automobile industry has a significant driving effect on the upstream and downstream economies. Promoting the construction of a green automobile manufacturing and management technology system is an important path for Indonesia to achieve coordinated development of economic growth and ecological protection. Based on the perspective of the entire life cycle of automobiles, this paper constructs a multidimensional model of the green manufacturing technology system from five dimensions: environmental carrying capacity, resource recycling, low-carbon energy substitution, economic cost optimization, and timeliness balance. Through a systematic analysis of the key technology systems required for the development of green automobiles, such as clean energy drive, lightweight design, and recycling remanufacturing, a localized implementation strategy is proposed. The study aims to provide a theoretical framework for Indonesia to reduce the carbon footprint of the automobile industry and enhance resource utilization efficiency, so as to help it enhance the international competitiveness of the manufacturing industry through green transformation, while alleviating the ecological and environmental pressures in the process of industrialization